2019
DOI: 10.1039/c9en00472f
|View full text |Cite
|
Sign up to set email alerts
|

Prospective environmental risk assessment of nanocellulose for Europe

Abstract: Quantitative environmental risk assessment of nanocellulose, using a dynamic and probabilistic modelling approach. Results show low risk, contributing towards the safe development of this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…With increasing use of nanocellulose (NC) in a wide range of industries and applications comes an increased likelihood of human exposure to this material during the various life stages of NC-containing products (Gottschalk and Nowack 2011). NC shows promise within a multitude of application fields, from healthcare to construction (Piccinno et al 2016;Stoudmann, Nowack, and Som 2019). NC can come from many different sources, ranging from wood pulp and cotton to food waste and algae.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing use of nanocellulose (NC) in a wide range of industries and applications comes an increased likelihood of human exposure to this material during the various life stages of NC-containing products (Gottschalk and Nowack 2011). NC shows promise within a multitude of application fields, from healthcare to construction (Piccinno et al 2016;Stoudmann, Nowack, and Som 2019). NC can come from many different sources, ranging from wood pulp and cotton to food waste and algae.…”
Section: Introductionmentioning
confidence: 99%
“…According to currently available information, the material poses no risk to human health or the environment. 47 Lignocellulose is a component of the cell walls of wooden plant parts and serves as a structural framework. The material consists of 40-80% cellulose, 5-25% lignin and 10-40% hemicellulose.…”
Section: Nr 52en | February 2020mentioning
confidence: 99%
“…Although some LCA analysis have suggested that the inhalation of NC would be the main exposure route for humans, more studies about the exposure concentrations or doses along the different stages, from NC production to customer use, are also required (Shatkin and Kim 2015;. Recently, studies have also quantitative determined the environmental release and risks of NC through the use of probabilistic material flow and environmental risk assessment models (Stoudmann et al 2019).…”
Section: Health Safety and Ecotoxicologymentioning
confidence: 99%